2007
DOI: 10.1080/17518420701309667
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of sex, age at burn, stage of adolescence, intelligence, position and degree of burn in thermally injured adolescents: Part 2

Abstract: A total of 44 thermally injured children (22 boys and 22 girls), currently aged 11-16 years old, who had been injured 3-14 years previously, stratified by age, sex, degree of burn (1-9%, 10-19%, 20%+) and position of burn (those whose burns included the face and those not burned facially) were selected from a sample pool of 394 previously hospitalized cases. Extent of psychological disturbance experienced by thermally injured adolescents and their mothers indicated that significant effects were evident regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Parents of daughters indicated more stress symptoms than parents of sons, which concurs with a study that found more guilt feelings among mothers of daughters compared with mothers of sons (Rivlin & Faragher, 2007). Furthermore, parents of older children within the preschool age range reported more PTSS, which was in agreement with another study on mothers of young children with burns (Mason & Hillier, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…Parents of daughters indicated more stress symptoms than parents of sons, which concurs with a study that found more guilt feelings among mothers of daughters compared with mothers of sons (Rivlin & Faragher, 2007). Furthermore, parents of older children within the preschool age range reported more PTSS, which was in agreement with another study on mothers of young children with burns (Mason & Hillier, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…[ 34 ] Published research into the outcomes of children living with scars have highlighted that the visibility of a scar, as well as its location and size, influence QoL. [ 41 44 ] However the impact of the scar on psychosocial adjustment and QoL appears to be related less strongly to clinically objective measures of severity or size, than to a child’s subjective perception of the significance of the scarring and, where relevant, to psychosocial functioning prior to scarring. [ 44 , 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents affected by burns often live with life-long social, educational, physical and psychological consequences (Rivlin & Faragher 2007 ; Weedon & Potterton 2011 ). They are vulnerable because of their maturing physical and psychosocial development (Russell et al .…”
Section: Introductionmentioning
confidence: 99%